1997
DOI: 10.1038/nm0997-1029
|View full text |Cite
|
Sign up to set email alerts
|

Nonadipose tissue production of leptin: Leptin as a novel placenta-derived hormone in humans

Abstract: Leptin is a circulating hormone that is expressed abundantly and specifically in the adipose tissue. It is involved in the regulation of energy homeostasis, as well as the neuroendocrine and reproductive systems. Here, we demonstrate production of leptin by nonadipose tissue, namely, placental trophoblasts and amnion cells from uteri of pregnant women. We show that pregnant women secrete a considerable amount of leptin from the placenta into the maternal circulation as compared with nonpregnant obese women. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
662
3
52

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,155 publications
(752 citation statements)
references
References 18 publications
35
662
3
52
Order By: Relevance
“…Placentally derived leptin is a potent stimulator of lipolysis (Masuzaki et al, 1997;Gomez et al, 1999;Fruhbeck et al, 2001) which the human placenta exports into both the maternal and fetal circulation (Linnemann et al, 2000;Hoggard et al, 2001). The rate of placental leptin export into the maternal circulation increases with increasing fetal to placental weight ratio (Hoggard et al, 2001), suggesting that the placenta may modulate its own substrate supply in response to the fetal demand.…”
Section: Maternalmentioning
confidence: 99%
“…Placentally derived leptin is a potent stimulator of lipolysis (Masuzaki et al, 1997;Gomez et al, 1999;Fruhbeck et al, 2001) which the human placenta exports into both the maternal and fetal circulation (Linnemann et al, 2000;Hoggard et al, 2001). The rate of placental leptin export into the maternal circulation increases with increasing fetal to placental weight ratio (Hoggard et al, 2001), suggesting that the placenta may modulate its own substrate supply in response to the fetal demand.…”
Section: Maternalmentioning
confidence: 99%
“…In fact, the administration of this hormone, while proven to be effective in reducing fat and normalizing metabolic disorders in leptin-deficient mice and humans, has not proven to be effective in most cases of obesity. 4,[8][9][10] Although leptin is mainly produced by the adipose tissue, this hormone is also produced by other tissues, such as stomach, [11][12][13] placenta, 14,15 skeletal muscle 16 and mammary epithelium, 17 and it is naturally present in maternal milk. 18,19 Although leptin produced by the adipose tissue is known to play a main role in the chronic control of energy balance, the role of leptin produced by the stomach has been related with the short-term control of food intake, acting as a satiety signal.…”
Section: Introductionmentioning
confidence: 99%
“…Our study further indicated that this pregnancyrelated increase in leptin concentration starts within the ®rst 2 ± 3 weeks after conception. It is suggested that the placenta is a major source of maternal leptin during pregnancy (Masuzaki et al, 1997;Sen Äaris et al, 1997). Considering the fast increase in leptin concentration during the ®rst weeks of pregnancy, other sources of leptin might be involved.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, a marked increase in the maternal serum leptin concentration occurs, which is followed by a sharp decrease immediately after delivery (Butte et al, 1997;Hardie et al, 1997;Sattar et al, 1998;Schrubing et al, 1998). Several studies have demonstrated that, aside from adipose tissue, the human placenta also synthesizes leptin (Masuzaki et al, 1997;Sen Äaris et al, 1997). Hormones like human chorionic gonadotrophin (hCG), luteinizing hormone (LH), estradiol and insulin may promote leptin release from maternal adipocytes and contribute to the hyperleptinemia (Hardie et al, 1997;Lepercq et al, 1998;Licinio et al, 1998;Sivan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%